Employee Protection Efforts Against Actions of Abuse and Violence in Securing Assets and Securing Company Asset Management (Case Study of PTPN IV Kebun Ajamu Unit) - Pahala Raja Situmorang; Muhammad Arif Sahlepi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore efforts to protect employees from acts of abuse and violence in the context of securing and managing company assets, with a special focus on PTPN Unit IV Kebun Ajamu. The method used is a qualitative approach and document analysis. Through this approach, research identifies incidents of abuse and violence recorded in letters of receipt of complaint reports. This research also highlights weaknesses in the implementation of existing asset security policies and procedures in companies. Research findings show that employees feel they are not adequately trained or prepared to deal with risky situations, and that there are communication and coordination problems between departments and between management and employees. This research also emphasizes the importance of integrating more sophisticated security technology and effective monitoring systems. Based on the research results, it is recommended that PTPN IV Kebun Ajamu improve security training and education for its employees, improve internal communications, and adopt more modern security technology. This research contributes to understanding the challenges and opportunities in efforts to protect employees and safeguard assets in the work environment